Clinical utility of diabetic ulcer severity score in surgical practice - Menezes, Jose V. Francisco; G. M., Sreenidhi; Vani K., Satya (International Surgery Journal, 2019)
Background: In surgical practice we come across many diabetic foot ulcer patients who often present late, leading to limb loss and even death. In the search for an effective screening tool to assess the severity of the disease and predict the outcome we have adopted the DUSS. Methods: Prospective study from October 2016 to April 2018 including 200 patients with diabetic foot ulcers conducted at Surgery Department in KIMS, Bangalore. DUSS was applied at the time of admission. DUSS comprises 4 clinical parameters: 1) pedal pulses, 2) probing to bone, 3) ulcer site and 4) ulcer number. These wounds were graded into score 0, 1, 2, 3, 4. Standard management was given to all patients according to a protocol. The outcome of treatment was recorded as healed ulcer, minor amputations, (toe or forefoot) or major amputations (below or above knee). Co-relation between the DUSS scores and final outcome was done. Results: Healing rates were higher in those with lower DUSS scores (88.9% in score 0 compared to 0% in Score 4). Minor amputation rates for scores 0, 1, 2,3 were 11.1%, 30.5%,28.3% and 44.1% respectively. Major Amputation rates were higher in patients with high DUSS scores i.e. 3 (41.8%) and 4 (100%). Conclusions: DUSS is an effective clinical tool to assess the severity of diabetic foot ulcers. DUSS scores help in predicting the outcome of treatment hence it can be used to counsel the patient regarding the disease and its prognosis. Patients with higher DUSS scores should require a more aggressive approach to minimise morbidity and mortality.